PERENCANAAN DINDING PENAHAN TANAH PADA AREA LONGSOR DI JALAN SYARANAMUAL DESA POKA KOTA AMBON - Rahantoknam, Wirda; Kumbangsila, Ruben; Betaubun, Renny James (Jurusan Teknik Sipil, 2024)
Syaranamual street is situated in Poka Village, Ambon . It is one of the provincial roads affected by landslides due to its location near a fairly high slope/cliff, precisely at Batu KonengÂ Fruit Market, Poka Village. The landslide disaster that occurred was due to the influence of bad weather in the form of high-intensity rain accompanied by strong winds that hit Ambon city, so a solution was needed in the form of planning the construction of a retaining wall. The research aims to plan the dimensions of the retaining wall and analyze and determine the safety factor for the stability of the retaining wall in the landslide area on Jl. Syaranamual, Poka Village, Ambon . The method used in this study is by using theory and also empirical formulas according to Rankine about active earth pressure and passive earth pressure on retaining walls and the Terzaghi method regarding soil bearing capacity. The study results show that the planned retaining wall is a gravity retaining wall with height (H) = 4 m, bottom width (B) = 2.4 m, top width (T) = 0.3 m, and Df = 0.5 m. The safety factor obtained from the calculation results is that the wall is stable against the shear force with a value of 2.2 > 1.5 (Safe), the wall is stable against the overturning force with a value of 2.03 > 1.5 (Safe), and the safety factor for the stability of the retaining wall obtained is 3 (Safe).